Differential expression of ribosomal proteins in myelodysplastic syndromes. Issue 2 (25th September 2015) - Rinker, Elizabeth B; Dueber, Julie C; Qualtieri, Julianne; Tedesco, Jason; Erdogan, Begum; Bosompem, Amma; Kim, Annette S
Abstract : Aberrations of ribosomal biogenesis have been implicated in several congenital bone marrow failure syndromes, such as Diamond–Blackfan anaemia, Shwachman–Diamond syndrome and Dyskeratosis Congenita. Recent studies have identified haploinsufficiency of RPS14 in the acquired bone marrow disease isolated 5q minus syndrome, a subtype of myelodysplastic syndromes (MDS). However, the expression of various proteins comprising the ribosomal subunits and other proteins enzymatically involved in the synthesis of the ribosome has not been explored in non-5q minus MDS. Furthermore, differences in the effects of these expression alterations among myeloid, erythroid and megakaryocyte lineages have not been well elucidated. We examined the expression of several proteins related to ribosomal biogenesis in bone marrow biopsy specimens from patients with MDS (5q minus patients excluded) and controls with no known myeloid disease. Specifically, we found that there is overexpression of RPS24, DKC1 and SBDS in MDS. This overexpression is in contrast to the haploinsufficiency identified in the congenital bone marrow failure syndromes and in acquired 5q minus MDS. Potential mechanisms for these differences and aetiology for these findings in MDS are discussed.